CBX1 as a Prognostic Biomarker and Therapeutic Target in Liver Hepatocellular Carcinoma: Insight into DNA Methylation and Non-Coding RNA Networks from Comprehensive Bioinformatics Analysis - Hye-Ran Kim; Jongwan Kim (Medicina, 2025)
Background and Objectives: Chromobox 1 (CBX1), a key epigenetic regulator involved in chromatin remodeling, has been implicated in various cancers; however, its role in liver hepatocellular carcinoma (LIHC) remains underexplored. This study aimed to investigate the expression patterns, epigenetic regulation, and non-coding RNA (ncRNA) networks involving CBX1 in LIHC, assess their potential as diagnostic and prognostic biomarkers, and explore their relevance as a putative therapeutic target. Materials and Methods: A multi-omics bioinformatics approach was employed using datasets from GEPIA2, OncoDB, UALCAN, Human Protein Atlas, KM Plotter, MethSurv, miRNet, and ENCORI. These databases were used to analyze mRNA and protein expression, DNA methylation, prognosis, and interaction networks involving CBX1 and ncRNAs. Results: CBX1 was significantly upregulated in both the mRNA and protein expression in LIHC. Upregulated CBX1 expression was associated with poor prognosis. DNA methylation analysis revealed that both hypermethylated and hypomethylated probes were significantly associated with CBX1 expression and poor prognosis. hsa-miR-212-3p and hsa-miR-132-3p were significantly upregulated in LIHC and were positively correlated with CBX1 expression and poor prognosis. The ncRNA network was identified, including long ncRNAs, circular RNAs, and pseudogenes, many of which were linked to tumor progression and poor prognosis, and competing endogenous RNAs were associated with tumor progression and poor prognosis in LIHC. Conclusions: CBX1 was significantly overexpressed in LIHC and was regulated by both DNA methylation and ncRNA interactions. Its expression is closely associated with a poor prognosis. The CBX1–micro-RNA–long ncRNA/circular RNA axis is a promising avenue for the development of novel diagnostic and therapeutic strategies. This study provides system-level insights into the regulatory landscape of CBX1 in LIHC and supports its potential role in precision medicine.